Gait, Balance, and Coordination Impairments in Niemann Pick Disease, Type C1. (January 2018) - Sansare, Ashwini; Zampieri, Cris; Alter, Katharine; Stanley, Christopher; Farhat, Nicole; Keener, Lee Ann; Porter, Forbes
This is the first study to objectively measure gait, balance, and upper limb coordination in a group of patients with NPC1 and compare the results to age and gender matched controls. This is also the first study to report effect sizes in these measures. Spatiotemporal gait analysis, static and dynamic posturography, and upper limb reaching motion analysis were performed. The findings showed that the NPC1 subjects had statistically significant deficits on 12 out of the 16 parameters investigated compared to controls, and large effect sizes for all but 1 parameter. When ranking the variables in terms of the effect sizes, the top 5 included at least 1 parameter from each of the 3 motor domains investigated. These results can provide insight to clinical researchers on the selection of outcome measures for longitudinal and interventional studies.